Challenges for Service Robots—Requirements of Elderly Adults with Cognitive Impairments - Korchut, Agnieszka; Szklener, Sebastian; Abdelnour, Carla; Tantinya, Natalia; Hernández-Farigola, Joan; Ribes, Joan Carles; Skrobas, Urszula; Grabowska-Aleksandrowicz, Katarzyna; Szczęśniak-Stańczyk, Dorota; Rejdak, Konrad (Frontiers in Neurology, 2017)
Objective: We focused on identifying the requirements and needs of people suffering from Alzheimer disease and early dementia stages with relation to robotic assistants. Methods: Based on focus groups performed in two centres (Poland and Spain) we created surveys for medical staff, patients, and caregivers, including: functional requirements; human-robot interaction, the design of the robotic assistant and user acceptance aspects. Using Likert scale and analysis made on the basis of the frequency of survey responses we identified users' needs as high, medium, and low priority. Results: We gathered 264 completed surveys (100 from medical staff, 81 from caregivers and 83 from potential users). Most of the respondents, almost at the same level in each of the three groups, accept robotic assistants and their support in everyday life. High level priority functional requirements were related to reacting in emergency situations (calling for help, detecting/removing obstacles) and to reminding about medication intake, about boiling water, turning off the gas and lights (almost 60% of answers). With reference to human-robot interaction, high priority was given to voice operated system and the capability of robotic assistants to reply to simple questions. Conclusion: Our results help in achieving better understanding of the needs of patients with cognitive impairments during home tasks in everyday life. This way of conducting the research, with considerations for the interests of three stakeholder groups in two autonomic centres with proven experience regarding the needs of our patient groups, highlights the importance of obtained results.